Alarming rates of virological failure and drug resistance in patients on long-term antiretroviral treatment in routine HIV clinics in Togo. (28th November 2015) - Konou, Abla A.; Dagnra, Anoumou Y.; Vidal, Nicole; Salou, Mounerou; Adam, Zakillatou; Singo-tokofai, Assétina; Delaporte, Eric; Prince-david, Mireille; Peeters, Martine
Abstract : Information on efficacy of long-term antiretroviral treatment (ART) exposure in resource-limited countries is still scarce. In 767 patients attending routine HIV centers in Togo and receiving first-line ART for more than four years, 42% had viral load greater than 1000 copies/ml and either were on a completely ineffective ART regime or were with only a single drug active. The actual conditions to ensure lifelong ART in resource-limited countries can have dramatic long-term outcomes.